Paraplegia due to Thoracic Mobile Schwannoma after Myelography - Akira Honda; Yoichi Iizuka; Tokue Mieda; Hiroyuki Sonoda; Sho Ishiwata; Yohei Kakuta; Daisuke Tsunoda; Eiji Takasawa; Tsuyoshi Tajika; Hiromi Koshi; Hirotaka Chikuda (Case Reports in Orthopedics)
Introduction. Spinal mobile tumors are very rare. We herein report a case of paraplegia caused by migration and incarceration of thoracic mobile schwannoma after myelography. Case Presentation. A 25-year-old man who had weakness and numbness in both his legs also had pain radiating to the back that was induced by back flexion or extension and jumping. Magnetic resonance imaging (MRI) showed an intradural extramedullary lesion at the T10 and T11 levels. Myelography was performed but discontinued due to his back and lower limb pain. Computed tomography after myelography revealed a rostrally migrated intradural mass with a discrepancy in the exact location in comparison to the MRI findings. He underwent a second lumbar puncture and drained the cerebrospinal fluid (CSF) to aid the spinal cord, because the symptoms gradually worsened and led to paraplegia. After the drainage of the CSF, his symptoms were immediately resolved. The day after myelography, he underwent complete resection of the tumor with the diagnosis of schwannoma. One year after the surgery, he had been working despite having hyperreflexia in his lower limbs with no weakness or sensory disturbance. Conclusion. Severe neurological deficits associated with spinal cord damage can occur due to migration of mobile tumors.